Critical Thinking Skills Enhancement: Implementation of CLIS Learning Models on Work and Energy - Oktavianty, Erwina; Silitonga, Haratua Tiur Maria; Marlina, Reni; Ridwan, Irwan Muhammad; Dirsa, Indah Sanita (KnE Social Sciences, 2024)
This study aimed to improve critical thinking skills (CTs) using the children learning in science (CLIS) model of students about work and energy at Junior Secondary School. The form of research used a pre-experiment with a one-group pretest-posttest design. The research participants were 28 students (eight grades) selected by using the intact group technique, randomly. The research instrument consisted of 6 essay questions. The result showed CTs students on work and energy was 49% in the medium category before the CLIS Lesson, while in the posttest it was 63% with the high category. Statistic descriptive analysis shows t count > t table, which means that Ho is rejected. It reveals a significant increase in the CTs of students. The increase in CTs in the CLIS model uses a gain score of 0.3 in the moderate category. So, it can be concluded that applying the CLIS model can improve CTs in energy and work materials. The CLIS model can be used as an alternative in the learning process to improve student’s CTs in work and energy materials. Keywords: critical thinking skills, CLIS learning models, work and energy